Effectiveness of Management Accounting System in Public Healthcare Sector: An Empirical Investigation in Vietnam - Ngo, Quang-Huy (Asian Journal of Business and Accounting, 2020)
Research aims: The purpose of this study is to investigate the impact of the decentralized structure on the effectiveness of MAS in the Vietnamese public healthcare sectors. Design/Methodology/Approach: Data collected from 165 respondents working at public healthcare organizations was used to test the proposed model. A PLS-SEM was used to assess the models. Assessment of common-method bias was also examined to ensure the findings' validity. Theoretical contribution/Originality: This study contributes to the MAS literature in Vietnam by extending previous studies' findings. This study also contributes to the contingency literature by assessing the effects of cartesian contingency mediation in MAS studies. Practitioner/Policy implication: This study provides some suggestions to practitioners, which strongly emphasizes the crucial role of the structure of healthcare organizations. Research limitation/Implication: The results subject to the limitation of generalizations and missing the pilot tests as well as the use of self-rating measuring performance.